Efficacy and Safety of Epidural Analgesia versus Traditional Analgesia for Relief of Labour Pain (KYAMC Journal, 2021)
Background: Labour pain, a form of acute pain, intensity of the pain is perceived by many women as very severe or intolerable especially in nulliparous. Providing effective and safe analgesia during labour has remained an ongoing challenge. Multiple pharmacologic and non-pharmacologic options are available to manage labour pain. Epidural analgesia have reported nearly complete pain relief with effective labour conduction.Objective: Purpose of this study was to evaluate the effectiveness of epidural analgesia and pethidine during labour and delivery.Materials & Methods: This cross sectional comparative study was conducted to compare the efficacy and safety between epidural and traditional analgesia on nulliparous women in labour. Subjects were grouped into two, group A received epidural & group B received traditional analgesia, each group comprising with 40 patients. Then the subjects were followed up and outcomes were recorded in a preformed data collection sheet.Results: The two groups were almost identical. Maternal age, gestational age and preinduction pain score (p = 0.127, p = 0.454 and p = 0.186 respectively). Study demonstrated earlier onset, pain score at different time intervals and the time of delivery were lower in epidural group than traditional (p < 0.001). No significant difference of complications (p = 0.431). Two(5%) patients in the epidural and five(12.5%) in the traditional group required caesarean delivery (p=0.455). No significance on neonatal outcome.Conclusion: Epidural analgesia induces a much earlier onset, intensity of pain reduced to a tolerable level and maintained up to delivery which not attained in the traditional method of analgesia.KYAMC Journal.2021;12(02): 66-70